2018
DOI: 10.1038/s41598-018-28983-w
|View full text |Cite
|
Sign up to set email alerts
|

Sub-nanoliter, real-time flow monitoring in microfluidic chips using a portable device and smartphone

Abstract: The ever-increasing need for portable, easy-to-use, cost-effective, and connected point-of-care diagnostics (POCD) has been one of the main drivers of recent research on lab-on-a-chip (LoC) devices. A majority of these devices use microfluidics to manipulate precisely samples and reagents for bioanalysis. However, filling microfluidic devices with liquid can be prone to failure. For this reason, we have implemented a simple, yet efficient method for monitoring liquid displacement in microfluidic chips using ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…PRADA score can then be integrated with artificial intelligence interfaces as well as smart phones for cost-effective health monitoring. 52,53 4 | MATERIALS AND METHODS…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRADA score can then be integrated with artificial intelligence interfaces as well as smart phones for cost-effective health monitoring. 52,53 4 | MATERIALS AND METHODS…”
Section: Discussionmentioning
confidence: 99%
“…Although this approach is limited by biomarker targets wherein the antigen structure is known and the location of a binding site on the target molecule can be predicted, we envision that PRADA will ultimately enable a precise scoring system to determine patient outcome. PRADA score can then be integrated with artificial intelligence interfaces as well as smart phones for cost‐effective health monitoring 52,53 …”
Section: Discussionmentioning
confidence: 99%
“…Imaging techniques are not popular in this category, as the adapter consists of special electronics that are designed specifically to target a unique chemical compound . Using a smartphone proved to be cost effective (see Figure 12), and extremely accurate results were reported when comparing the performance of the smartphone‐based adapters to those of laboratory equipment and devices with a low CV%, a high regression coefficient, lower costs, and a low LOD (see Figures to ) . Zhao et al, as shown in Figure A, developed a fluorescent smartphone‐based label‐free sensor to detect Fe (III) by employing the quenching effect.…”
Section: Resultsmentioning
confidence: 99%
“…[168][169][170][171][172][173][174] Using a smartphone proved to be cost effective (see Figure 12), and extremely accurate results were reported when comparing the performance of the smartphone-based adapters to those of laboratory equipment and devices with a low CV%, a high regression coefficient, lower costs, and a low LOD (see Figures 10 to 13). [175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192] Zhao et al, 193 as shown in Figure 8A, developed a fluorescent smartphone-based label-free sensor to detect Fe (III) by employing the quenching effect. The 3D printed adapter uses a 365-nm UV LED and a smartphone camera.…”
Section: Electrochemical Applicationsmentioning
confidence: 99%
“…There have been plenty of studies on capillary microfluidic devices with different materials and fabrication methods: paper-based [ 8 , 9 , 10 , 11 , 12 ], polymer-based [ 13 , 14 ], and 3D-printed devices [ 15 ], etc. The recent studies of Delarmarche and colleagues have highlighted the potential of silicon-based capillary-driven devices, given their robust fabrication, good chemical resistance, and versatile surface coating methods [ 16 , 17 ]. Hence, it is still favorable, especially in research areas.…”
Section: Introductionmentioning
confidence: 99%